Психологічні аспекти десоціалізації особистості в підлітковому віці - Воробйова, І. В.; Vorobyova, I. V.; ORCID: http://orcid.org/0000-0003-0325-7744; Ларіонов, С. О.; Larionov, S. O.; ORCID: http://orcid.org/0000-0002-3027-8535 (Право і безпека. – 2016. – № 3 (62). – С. 125–129, 2016)
Здійснено теоретичний огляд проблеми десоціалізації особистості в підлітковому віці. Проаналізовано закономірності та механізми нормативного психічного розвитку в підлітковому віці, провідні мотиви й інтереси підлітків. Розкрито зміст понять «соціалізація» та «десоціалізація», механізми й закономірності соціалізації та її дефектів у підлітковому віці. Проаналізовано закордонні та вітчизняні теорії десоціалізації підлітків.

Theoretical overview of the problem of the de-socialization of personality in the age of adolescence has been implemented. The patterns and mechanisms of normative mental development in the age of adolescence, the dominant motives and interests of youngsters have been analyzed. It has been demonstrated that the key psychological process of the age of adolescence is growing-up, which is to overcome the inconsistencies between the existing mental and behavioral abilities of an individual and the requirements of the “adult” society. Most indicative objective elements of growing-up are attitudes of a minor to various aspects of reality; they are formed on the basis of the subjective experience of adulthood. It has been demonstrated that the development of personality in the age of adolescence occurs as farther – as the less under the influence of the processes of learning and education, and as more under the influence of the socialization process, in small groups of communication. Mechanisms and patterns of this process have been demonstrated. The content of the notion of the de-socialization, its mechanisms and patterns in the age of adolescence have been revealed. The generalization of the results of experimental studies, presented in the scientific psychological literature, allowed to present features of the de-socializied minor and an indicative list of his psychological characteristics.

Осуществлён теоретический обзор проблемы десоциализации личности в подростковом возрасте. Проанализированы закономерности и механизмы нормативного психического развития в подростковом возрасте, доминирующие мотивы и интересы подростков. Раскрыты содержание понятий «социализация» и «десоциализация», механизмы и закономерности социализации и её дефектов в подростковом возрасте. Проанализированы зарубежные и отечественные теории десоциализации подростков.
Psychological aspects of the de-socialization of personality in the age of adolescence
Психологические аспекты десоциализации личности в подростковом возрасте
Воробйова, І. В. Психологічні аспекти десоціалізації особистості в підлітковому віці / І. В. Воробйова, С. О. Ларіонов // Право і безпека. – 2016. – № 3 (62). – С. 125–129.
Воробйова І. В., Ларіонов С. О. "Психологічні аспекти десоціалізації особистості в підлітковому віці." Право і Безпека 3 (2016): 125-129.
Vorobyova, I.V. and Larionov, S.O. (2016), “Psychological aspects of the de-socialization of personality in the age of adolescence” [“Psykholohichni aspecty desotsializatsii osobystosti v pidlitkovomu vitsi”], Pravo i Bezpeka, No. 3, pp. 125–129.
Keywords: Психологія. Рsychology. Психология; Наукові публікації. Scientific publications. Научные публикации; соціалізація; десоціалізація; підлітки; дорослішання; socialization; de-socialization; youngsters; growing-up; социализация; десоциализация; подростки; взросление